Two new genera and six new species of Terrestrial Hydrometridae (Hemiptera: Heteroptera) from French Polynesia - Polhemus, Dan A. (Zootaxa, 2022)
The family Hydrometridae (Hemiptera: Heteroptera) has been previously recorded from French Polynesia based on three species in three genera: Chaetometra robusta (Hungerford, 1939) and Dolichocephalometra pacifica (Van Duzee, 1934) from the Marquesas Islands, and Hydrometra gagnei J. Polhemus & D. Polhemus, 1995 from Tahiti in the Society Islands. Based on recent surveys from montane cloud forest habitats, two new genera and and six new species of Hydrometridae are described from the Marquesas and Society Islands as follows: Marquesametra n. gen. from the Marquesas Islands, containing M. hivaoa n. sp. from Hiva Oa (Mt. Temetiu); and Prohydrometra n. gen. from the Society Islands, containing the previously described P. gagnei n. comb. from Tahiti (Tahiti Nui), and the five new species P. johnpolhemi n. sp. and P. englundi n. sp. from Raiatea (Trois Cascade and Mt. Toomaru respectively); P. tohiea n. sp. and P. moorea n. sp. from Moorea (both from Mt. Tohiea); and P. teatara n. sp. from Tahiti (Mts. Teatara). All of these new species are terrestrial, and with the exception of P. johnpolhemi, which inhabits rheocrenes, represent specialized inhabitants of upland wet forest habitats. This indicates that terrestrial ecologies have evolved multiple times within the Hydrometridae, and are the typical mode of life for species of this family occurring in the insular eastern Pacific.